Application of gamal Gliricidia sepium leaves compost as depuration agent of leads (Pb) in the body organ of red tilapia Oreochromis sp. - , Robin; Kukuh Nirmala; Enang Harris; Ridwan Affandi; Dedi Jusadi (Jurnal Akuakultur Indonesia)
ABSTRACT